Developing a Renewable Energy-Theme English-Speaking Module for Senior High School Students - Suprayetno, Edi; Ramadhani, Maitri (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
Developing students' speaking competence remains challenging in English language teaching, particularly when lessons lack authentic contexts connecting learning to real-world issues. This study aimed to design and validate a web-based e-module integrating renewable energy themes to support Grade XI students' speaking skills while fostering ecological awareness. Guided by Content-Based Instruction and Eco-linguistics principles, this Research and Development (R&D) study followed the Borg and Gall model, conducted in two senior high schools (SMA N.1 Hinai and SMA N.1 Gebang) in Langkat, North Sumatra. Data were collected through expert validation sheets, questionnaires, classroom observations, and semi-structured interviews involving 60 students and 8 English teachers, then analyzed using descriptive statistics and thematic analysis. The development process encompassed expert validation, small-scale trials, and classroom implementation. Expert reviews confirmed high validity across content, language, and instructional technology dimensions (M = 90.35%,